RESPON PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays Saccharata Sturt) TERHADAP PEMBERIAN PUPUK KANDANG KAMBING DAN NPK DI DESA SUROREJAN - Habib Ahmad Fahrezi; Rennanti Lunnadiyah Aprilia (Nusantara Hasana Journal, 2025)
Sweet corn (Zea mays Saccharata Sturt) is a popular horticultural crop among the community. However, sweet corn production in Kebumen experienced a decline from 2021 to 2023. One method to increase production yield is by applying the appropriate and balanced fertilizer dosage. This study aims to analyze the growth response and yield of sweet corn to the application of goat manure and NPK fertilizer in Surorejan Village. The research method used was a completely randomized block design with two treatment factors: goat manure (P) and NPK 16-16-16 fertilizer (N). The P factor consisted of four treatment doses: P0 (0 kg/m²), P1 (1 kg/m²), P2 (2 kg/m²), and P3 (3 kg/m²). The N factor had four treatment levels: N0 (0 kg/m²), N1 (0.01 kg/m²), N2 (0.02 kg/m²), and N3 (0.03 kg/m²). The observed data were analyzed using SPSS. If significant differences were found, further analysis was conducted using the 5% DMRT test to determine the best treatment. The results showed that goat manure and NPK 16-16-16 fertilizer did not have a significant effect on the growth of sweet corn (Zea mays Saccharata Sturt). However, the P3 treatment showed a significant difference in the yield of sweet corn.